2021
DOI: 10.1097/sih.0000000000000546
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of High-Technology Into the Stop the Bleed Program Among School Personnel Improves Short-Term Skill Application, Not Long-Term Retention

Abstract: Introduction:The Stop the Bleed (STB) program trains the general public on identifying and treating life-threatening bleeding. Data on efficacy and retention of skills taught through this program are limited, with the role of high-technology modalities to augment the program, such as simulation and feedback devices, untested. Methods: A convenience sample of 66 school personnel participated in an open-label observational study from January to August 2019. The control group received the standard bleeding contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…When a group of potential lay responders who had previously undergone the American College of Surgeons Bleeding Control Course were reassessed, adequate hemorrhage control performance was delivered less than 4% of the time [ 33 ]. Further, poor retention of hemorrhage control skills as soon as three months after training was also noted by both Jafri and Goralnick in controlled studies [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…When a group of potential lay responders who had previously undergone the American College of Surgeons Bleeding Control Course were reassessed, adequate hemorrhage control performance was delivered less than 4% of the time [ 33 ]. Further, poor retention of hemorrhage control skills as soon as three months after training was also noted by both Jafri and Goralnick in controlled studies [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 75%
“…The cost of Caesar, the trauma patient, is relatively high and difficult to obtain, which imposes some restrictions on the implementation of teaching. In addition, many studies have shown that although the STB course can effectively improve students’ trauma haemostatic skills, the retention of these skills was poor [ 7 , 37 , 38 ]. Therefore, increasing the retention of skills is extremely important for improving the mastery rate of trauma haemostasis skills.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the interactive nature of the mobile application, CPR skill performance has also been shown to improve with use of feedback devices (Lin & Cheng, 2015; Jafri et al, 2021). With use of the app, participants practiced CPR procedures in an interactive, simulated manner, with direct feedback after each session based on their performance.…”
Section: Discussionmentioning
confidence: 99%